Integrating Wayground in teaching short functional texts: Impacts on students’ motivation - Destriana, Melisa; Farida, Alief Noor (ELT Forum: Journal of English Language Teaching, 2025)
In digital era, everything generated with internet and apps which has crucial role in daily activity. Not only in a daily basis, but also in education area needs to change due to the circumstance. Especially when it comes to learn, the teacher needs to follow the trend to maintain the students’ motivations to learn, so that it will help them to understand the problem in English class and creating good grade. This could happen if the teacher tries to be understood the students need and start using digital learning method than the conventional. This study aims to evaluate the use of Wayground as a digital learning medium in teaching short functional texts and to explore its impact on the learning motivation of eighth-grade students at one public junior high school in Cepu, a city in Central Java, Indonesia. A qualitative descriptive approach was applied, with data collected through observation, teacher interviews, and student questionnaires. The results show that integrating Wayground into English lessons significantly enhances student interest and engagement, particularly in writing skills. Most students responded positively to the interactive format, stating that learning became more enjoyable and motivating. These findings suggest that digital tools like Wayground can be effective in creating a more dynamic and student-centered learning environment.